IMPLIKASI HAK ATAS TANAH MASYARAKAT ADAT DALAM PENYELENGGARAAN KEGIATAN PERTAMBANGAN MINERBA DI INDONESIA - Mustofa, Ragil; Anita, Anita (Jurnal Jendela Hukum, 2025)
Mineral and coal mining (minerba) is a very important industry and plays a major role in the national economy. However, in practice, mining activities often cause disputes with land rights holders, both individuals and communities. These disputes are generally caused by overlapping between mining rights granted by the government and land rights recognized by law. This study aims to examine the legal framework governing land rights in minerba mining operations and highlight the legal consequences arising from disputes between holders of Mining Business Permits (IUP) and landowners or land controllers. The study employs a normative approach using a legal framework and case analysis. In this case, it shows that the lack of harmony between mining law and land law has caused legal uncertainty, especially for communities living in mining concession zones. The state, which has authority over natural resources, often ignores the principles of distributive justice and protection of land rights. Therefore, it is important to harmonize the provisions of the Minerba Law with the Basic Agrarian Law, as well as establish a fair and inclusive dispute resolution process. This study urges the enhancement of land rights recognition within the mining licensing framework to improve legal clarity and social justice.